Chickpea production in response to fertilization with zinc and doses of phosphorus - Fonseca, Jorge Henrique dos Santos; Almeida Neta, Maria Nilfa; Pegoraro, Rodinei Facco; Almeida, Gbison Ferreira de; Costa, Cândido Alves da; Almeida, Elaine Soares de (Comunicata Scientiae, 2020)
Chickpea cultivation in Brazil has not yet been consolidated, and studies aiming at the adequate nutritional management for this crop are necessary. This work aimed to evaluate the production of chickpea plants (cultivar BRS Aleppo) subjected to fertilization with zinc and P doses. The experimental was completely randomized, with four replications, in a 3 x 5 factorial scheme, corresponding to three fertilization treatments with Zn (without Zn addition; 50% of Zn applied at sowing, via soil + 50% applied at flowering, via leaves; and 100% applied at sowing, via soil) and five doses of phosphorus (0, 60, 120, 180, and 240 kg ha-1 of P2O5). The 100-grain mass (M100), pod mass (MV), number of pods (NV), number of grains (NG), total grain mass (MGT), yield (PROD), dry matter of the shoot part (MSPA) and plant residues (MSRV), and agronomic efficiency (EA) were characterized. There was an isolated effect of the P doses on the M100, MGT, PROD, MSPA, and MSRV characteristics. The application of 240 kg ha-1 resulted in an increase in the production components and a maximum yield of 3,018 kg ha-1, indicating the need to adopt higher doses of P2O5 to increase chickpea production in tropical soils. However, the highest agronomic efficiency was obtained after the application of 60 kg ha-1 of P2O5, along with Zn at sowing.